THE CHLOROPHYLL-CARBON DIOXIDE RATIO DURING PHOTOSYNTHESIS - McAlister, E. D. (The Rockefeller University Press, 1939)
Using a rapid spectrographic method of carbon dioxide measurement previously described by McAlister (1937) further studies on the time course of photosynthesis in the higher plant, wheat, variety Marquis, are herein reported. Of major importance in this work is the discovery of a pick-up of carbon dioxide in darkness immediately following a high rate of photosynthesis (see Figs. 3 and 4). This pick-up is believed to be due to the action of a carbon dioxide-combining intermediate; i.e., the "acceptor molecule" for carbon dioxide in photosynthesis. The conditions under which this phenomenon has so far been observed indicate that the intermediate is formed in relatively large quantities during the actual process of photosynthesis and not before. That the intermediate is chlorophyllous in nature is suggested by a simple stoichiometry of the order of unity that is found to exist between the number of carbon dioxide molecules taken up and the total number of chlorophyll molecules present in the plant. This is in opposition to the idea of a large photosynthetic unit of some 2000 chlorophyll molecules operating together in the reduction of 1 carbon dioxide molecule. Further studies of the induction phase under various conditions of previous dark rest and of carbon dioxide and light limitation are herein described. Employing the simple hypothesis that the number of carbon dioxide molecules not reduced during the induction period (induction loss) gives a measure of the number of elementary photosynthetic cycles unoperative or compensated for during induction together with the experimental fact that this induction loss is of the order of the total number of chlorophyll molecules present, these latter studies also indicate, in a less direct manner, that chlorophyll participates in photosynthesis as an individual molecule and not as part of a very large multimolecular chlorophyll unit. The fast dark reaction lasting about 1 minute (Fig. 7) required to reproduce both (a) the phenomena of induction in carbon dioxide assimilation and (b) the recovery of fluorescence of chlorophyll in leaves in darkness as observed by Franck and Wood (1936), demonstrates a close relationship between the fluorescence of chlorophyll and induction in photosynthesis. The rate of respiration (carbon dioxide production) of the higher plant, wheat, was measured under intense illumination and in the absence of carbon dioxide (to suppress assimilation). This value was found to be identical with the dark respirational rate measured before and after the light period, indicating very positively the absence of any direct effect of light on respiration.